Graphical Smooth Switching Control Method of Four-Switch Buck-Boost Converter in Fuel Cell Systems - Hongwei Feng; Yuanyuan Liu; Chunping Guo; Ye Li; Tai Li (IEEE Access)
This paper proposes a graphical smooth switching control method for a four-switch Buck-Boost (FSBB) converter in fuel cell systems. Traditional FSBB converters can reduce average inductance current in multi-mode operations. However, maintaining high efficiency across the full load range remains challenging. Additionally, voltage gain dead spots during mode switching lead to poor dynamic performance and stability. To address these issues, this article first analyzes the four-mode working process of FSBB converters and explores the causes of voltage gain dead spots through graphical methods, then an innovative four-mode graphical control strategy is proposed, which effectively eliminates voltage gain dead spots and achieves smooth switching by introducing Buck-Boost Buck mode and Buck-Boost Boost mode. In addition, in order to accelerate the response speed during the system mode switching process and solve the problem of sudden duty cycle changes, this paper designs input voltage feedforward functions for each of the four working modes based on the voltage-current dual loop PI control, greatly enhance the controller’s response speed and effectively reducing the output voltage fluctuation during the mode switching process. The experimental results fully verify the effectiveness and progressiveness of the control strategy, and provide scientific basis and technical support for the efficient and stable operation of FSBB converter in the fuel cell systems.